Periodismo en internet : como escribir y publicar contenidos de calidad en la red - Jaraba, Gabriel (Barcelona Ma Non Troppo, 2014)
New technologies have made our lives increasingly connected to information; new forms of entertainment and socializing revolve around communication. This is a book for journalism and communication students interested in communicating and being heard. Professionals wanting to adopt new technologies and anyone with cultural concerns who have discovered that the internet is an immense field of learning and actions will also find this book helpful. Each chapter is a gradual introduction that shows how to acquire and practice new communication skills. Learn how to adapt journalistic writing to websites and discover resources to better use social media outlets.
Keywords: Periodismo electrónico; Internet